Stabilisasi Tanah Gambut Dengan Kapur Dan Abu Terbang Untuk Mengurangi Kebakaran Lahan - Toni, Afriwan; Muhardi, Muhardi; Wibisono, Gunawan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Fires in peat land in Riau Province commonly happened in the dry season and the water level of peat land was low. To reduce the risk of fires in peat soil can be implemented with the solidification and stabilization. Stabilization of peat soil by used additive ingredients such as chalk (CaCo3) and fly ash was one method of soil stabilization. The Additive ingridients could improve the technical properties and filled the voids in the peat soil was reduced. This research was aimed to determine the optimal composition content of chalk and fly ash to the stabilization of burning peat soil. The optimum water content for compaction was range between 100% and 160%, Hadijah (2006) in Ilyas (2008). Based on literature, this research using 100% water content for compaction. The pure peat soil was burned at the optimum water content and temperature obtained burning point at 72 °C within 4 minutes. After peat stabilization with fly ash 15% and 5% CaCO3, burning point was much longer to 94 °C within 34 minutes. Higest point of ash happened on peat soil with fly ash 15% and CaCo3 5% with a temperature of 206 °C and within 59 minutes. Meanwhile, ingredient content such as peat soil+ 5% CaCo3 + 10% fly ash, peat soil + 5% caco3 + 5% fly ash, and on pure peat soil has a short time. It was because the fly ash and chalk can be reduced the burning process time.Keywords: Peat Soils, Fly Ash, Chalk, Burning Point, Ash Point